Vedolizumab Efficacy Is Associated With Decreased Intracolonic Dendritic Cells, Not Memory T Cells - Boden, Elisa K; Kongala, Ramya; Hindmarch, Duncan C; Shows, Donna M; Juarez, Julius G; Lord, James D (Inflammatory bowel diseases, 2024)
Abstract Background Vedolizumab, an antibody blocking integrin α4β7, is a safe and effective therapy for Crohn’s disease and ulcerative colitis. Blocking α4β7 from binding its cognate addressin MAdCAM-1 on intestinal blood vessel endothelial cells prevents T cells from migrating to the gut mucosa in animal models. However, data supporting this mechanism of action in humans is limited. Methods We conducted a cross-sectional case-control study to evaluate the effect of vedolizumab on intestinal immune cell populations while avoiding the confounding effect of resolving inflammation on the cellularity of the colonic mucosa in treatment-responsive patients. Colon biopsies from 65 case subjects receiving vedolizumab were matched with biopsies from 65 control individuals, similar in disease type, medications, anatomic location, and inflammation. Biopsies were analyzed by flow cytometry and full messenger RNA transcriptome sequencing of sorted T cells. Results No difference was seen between vedolizumab recipients and control individuals in the quantity of any antigen-experienced T lymphocyte subset or in the quality of the transcriptome in any experienced T cell subset. Fewer naïve colonic B and T cells were seen in vedolizumab recipients than control individuals, regardless of response. However, the most striking finding was a marked reduction in CD1c+ (BDCA1+) dendritic cells exclusively in vedolizumab-responsive patients. In blood, these dendritic cells ubiquitously express high levels of α4β7, which is rapidly downregulated upon vedolizumab exposure. Conclusions The clinical effects of vedolizumab reveal integrin α4β7-dependent dendritic cell migration to the intestinal mucosa to be central to inflammatory bowel disease pathogenesis. Lay Summary Vedolizumab had no effect on the number or gene expression of memory T lymphocytes in the colons of recipients relative to control individuals. However, the colons of vedolizumab-responsive patients had distinctly fewer dendritic cells, which in blood express the most integrin α4β7.